RETRACTED: LINC01315 Impairs microRNA-211-Dependent DLG3 Downregulation to Inhibit the Development of Oral Squamous Cell Carcinoma - Chen, Fu-Bo; Wu, Peng; Zhou, Rong; Yang, Qi-Xiang; Zhang, Xu; Wang, Rao-Rao; Qi, Sheng-Cai; Yang, Xi (Frontiers in Oncology, 2020)
Recent studies have revealed that long non-coding RNAs (lncRNAs) involve in the progression of oral squamous cell carcinoma (OSCC). These lncRNAs have emerged as biomarkers or therapeutic targets for OSCC. We here aimed to investigate the role of lncRNA LINC01315 in OSCC and the related mechanisms. LINC01315 and DLG3 were determined to be poorly expressed while microRNA-211 (miR-211) was highly expressed in OSCC tissues and cells using RT-qPCR and western blot analysis. Based on the results obtained from dual-luciferase reporter gene, RIP, and FISH assays, LINC01315 was found to upregulate DLG3 expression by competitively binding to miR-211. Upon altering the expression of LINC01315, and/or miR-211 in OSCC cells with shRNA, mimic, or an inhibitor, we assessed their effects on OSCC cell proliferation, migration, invasion, and apoptosis. LINC01315 knockdown enhanced OSCC cell proliferation, migration and invasion, but dampened their apoptosis, all of which could be reversed by miR-211 inhibition. Elevation of DLG3, a target gene of miR-211, activated the Hippo signaling pathway, whereby suppressing OSCC progression in vitro. Finally, their roles in tumor growth were validated in vivo. These findings suggest that LINC01315 elevates DLG3 expression by competitively binding to miR-211, thereby suppressing OSCC progression.